Aspects of Molecular Genetics in Dromedary Camel - Piro, Mohammed (Frontiers in Genetics, 2021)
Dromedary camels are unique in their morphological and physiological characteristics and are capable of providing milk and meat even under extreme environmental conditions. Like other species, the dromedary camel has also benefitted from the development of the molecular genetics to increase the knowledge about different aspect in camel genetics (genetic variation, molecular marker, parentage control, gene of interest, whole genome, dating…etc). In this paper we review the different molecular genetic technics used in this particular species and future prospects. Dromedary genetic studies started in the end of the 1980s with phenotypic evaluation and the attempts to highlight the protein and biochemical diversity. In the 2000s, with the development of molecular markers such as microsatellites, genetic diversity of different types in several countries were estimated and microsatellites were also used for parentage control. In terms of genetic characterization, microsatellites revealed a defined global structure, differentiating East African and South Arabian dromedaries from North African, North Arabian, and South Asian individuals, respectively. Also, mitochondrialDNA sequence analysis of ancient DNA proved to be crucial in resolving domestication processes in dromedaries. Ancient and modern DNA revealed dynamics of domestication and cross-continental dispersion of the dromedary. Nuclear SNPs, single nucleotide polymorphisms changes that occur approximately each 1000 bps in the mammalian genome were also applied in some studies in dromedary. These markers are a very useful alternative to microsatellites and have been employed in some studies on genetic diversity and relevant phenotypic traits in livestock. Finally, thanks to the use of Next Generation Sequencing (NGS) the whole-genome assemblies of the dromedary (Camelus dromedarius) and a work to establish the organization of the dromedary genome at chromosome level were recently published.